KEMAMPUAN KETERAMPILAN DASAR MENGAJAR MAHASISWA CALON GURU IPA PROGRAM STUDI PENDIDIAN IPA - Indri Nurwahidah (Unit Pelaksana Praktik Kependidikan Terpadu Fakultas Keguruan dan Ilmu Pendidikan Universitas Muhammadiyah Riau, 2020)
The application of basic teaching skills is very important to do by the teacher so that the delivery of learning materials can run smoothly, effectively, efficiently, and professionally. The aim of this research was to determine the ability of the basic teaching skills of prospective science teacher in microteaching class. This type of research is a descriptive qualitative to describe descriptively the ability of basic teaching skills prospective science teacher in microteaching class. Based on the results of this research could be define that the average value of basic teaching skills in the first or second teaching practise was 67 categorized as good. It can be concluded that the average ability of basic teaching skills of prospective science teacher students in the Ivet University IPA education study program is in the good category.